Mitigation of ammonium toxicity by silicon in tomato depends on the ammonium concentration - Barreto, R. F. [UNESP] (2016)
Ammonium toxicity in hydroponically grown crops can affect tomato development. However, it has been shown that the silicon (Si) attenuates ammonium toxicity in plants depending on the plant species, the stage of development and the ammonium concentration in the nutrient solution. Thus, in order to investigate how Si attenuates stress caused by ammonium in tomato, a study was carried out involving plants cultivated up to 40 days after seed germination using nutrient solutions containing ammonium concentrations (1, 2, 4, 6 and 8 mmol L-1), in the absence or presence of Si (1 mmol L-1). The accumulation and efficiency of nitrogen and Si use, as well as the concentrations of chlorophyll, carotenoids, malondialdehyde, hydrogen peroxide and growth parameters was assessed. At a concentration of 1 mmol L-1 ammonium, Si increases the accumulation of nitrogen and Si, the nitrogen use efficiency, the root area and dry biomass of the shoot. At concentrations of 1 and 2 mmol L-1 ammonium, Si increases the leaf area and root dry biomass, and in higher concentrations, there was no effect of Si after the supply of ammonium. It was observed that the addition of Si mitigates ammonium toxicity by 1 mmol L-1 ammonium, and we can recommend its use in the nutrient solution (Si = 1 mmol L-1) to grow tomato cropsthat employs ammonium concentration of 1 mmol L-1.